Sindrome hipertensivo del embarazo en ecuador y latinoamerica - Kirby Ojeda, Cristhian Paul (Machala : Universidad Técnica de Machala, 2019)
Introduction: Worldwide hypertensive syndromes are one of the most frequent complications of pregnancy and are one of the main causes of maternal and neonatal morbidity and mortality, especially in the population with few resources. They have a progressive presentation, of still unknown cause and different predisposing factors. In Ecuador, it is one of the leading causes of morbidity and mortality, chronic disability, mortality of the fetus and newborn. Preeclampsia and eclampsia have been the leading cause of maternal death in our country from 2006 to 2014. In Latin America and the Caribbean, hypertensive disorders are responsible for at least 26% of maternal deaths. Objective: To establish the prevalence of hypertensive syndromes of pregnancy in Ecuador and Latin America. Materials and methods: The present study has been conducted based on a systemic investigation such as: Biomed Central, CINAHL, Cochrane Library, Embase, HMIC, Medline and WHO records, ClinicalTrials.gov, Pubmed, Mesh, Google Schoolar, American Journal of Obstetrics and Gynecology. Results and conclusion: the study was conducted in pregnant women with hypertensive syndrome problems with an average age of 26 ± 6 years. The specific cause of hypertensive disorders in pregnancy has not yet been identified, however, the incomplete invasion of the trophoblast has become a point of confluence between the various theories that aim to explain its etiopathogenesis.
Introducción: A nivel mundial los síndromes hipertensivos constituyen una las complicaciones más frecuentes del embarazo y son una de las principales causas de morbimortalidad materna y neonatal, especialmente en la población de escasos recursos. Tienen una presentación progresiva, de causa aún desconocida y distintos factores predisponentes. En el Ecuador es una de las primeras causas de morbimortalidad, discapacidad crónica, mortalidad del feto y recién nacido. La preeclampsia y eclampsia han sido la primera causa de muerte materna en nuestro país desde el año 2006 al 2014. En América Latina y el Caribe, los trastornos hipertensivos son responsables de al menos el 26% de las muertes maternas. Objetivo: Establecer la prevalencia de los síndromes hipertensivos del embarazo en Ecuador y Latinoamérica. Materiales y métodos: El presente estudio se ha realizado en base a una investigación sistémica como: Biomed Central, CINAHL, Cochrane Library, Embase, HMIC, Medline y registros de la OMS, ClinicalTrials.gov, Pubmed, Mesh, Google Schoolar, American Journal of Obstetrics and Gynecology. Resultados y conclusión: el estudio se realizó en mujeres embarazadas con problemas de síndrome hipertensivo en un promedio de edad de 26 ± 6 años. Aún no se ha podido identificar la causa específica de trastornos hipertensivos en el embarazo, no obstante, la invasión incompleta del trofoblasto se ha constituido en un punto de confluencia entre las diversas teorías que pretenden explicar su etiopatogenia.
Keywords: COMPLICACIONES DEL EMBARAZO; PREECLAMPSIA; ECLAMPSIA; MORBIMORTALIDAD